2015
DOI: 10.1093/aobpla/plw063
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity driven by morphological and ecological disparity: a case study of comparative seed morphology and anatomy across a large monocot order

Abstract: The banana and ginger group, order Zingiberales, comprises of exceptionally diverse, primarily tropical, plants. Within Zingiberales, the ginger family (Zingiberaceae) is unique in being not only the most species-rich but also the most disparate in terms of their morphology and anatomy, and the only group with a substantial number of species in temperate environments. Multiple radiations into temperate habitats were found to not be driven by morphological change, but instead may point to a genetic plasticity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Seed myxospermy is an advanced trait with an origin that may extend back to the Eocene, a geologic epoch with climatic variability and vegetation adaptation to long-term warming also evident from fossil fruits and seeds (Collinson et al, 2012;Smith et al, 2009b). SRXTM imaging of fossil (Friis et al, 2019;Friis et al, 2014;Manchester and Collinson, 2019;Smith et al, 2009b) and modern (this work and Arshad et al, 2020;Benedict et al, 2016;Smith et al, 2009b) flowers, seeds and fruits revealed internal structures that may have evolved as adaptations to climatic change and variable environments Linkies et al, 2010;Walck et al, 2011).…”
Section: Aethionema Arabicum As a Dimorphic Model For Sce Development And Differentiation In Mucilage Productionmentioning
confidence: 85%
“…Seed myxospermy is an advanced trait with an origin that may extend back to the Eocene, a geologic epoch with climatic variability and vegetation adaptation to long-term warming also evident from fossil fruits and seeds (Collinson et al, 2012;Smith et al, 2009b). SRXTM imaging of fossil (Friis et al, 2019;Friis et al, 2014;Manchester and Collinson, 2019;Smith et al, 2009b) and modern (this work and Arshad et al, 2020;Benedict et al, 2016;Smith et al, 2009b) flowers, seeds and fruits revealed internal structures that may have evolved as adaptations to climatic change and variable environments Linkies et al, 2010;Walck et al, 2011).…”
Section: Aethionema Arabicum As a Dimorphic Model For Sce Development And Differentiation In Mucilage Productionmentioning
confidence: 85%
“…Previous studies have reported evidence for and against the relationship between morphological rate of evolution and speciation in vertebrates (Adams et al, 2009;Rabosky et al, 2013;Kozak & Wiens, 2016b). Studies on plants have looked at speciation in relation to morphological variation in a single organ (Dodd et al, 1999;Benedict et al, 2016;Marcussen & Meseguer, 2017), yet there has been little research comparing the rate of morphological evolution across multiple organ types with the rate of diversification. Our study assessed the average rate of evolution (as the number of changes per variable character per million years) of both macro-and micromorphology across the entire plant and compared the rate with the species richness per disjunct sister.…”
Section: Species Diversity Anomaly and Relationship Between Rate Of Dmentioning
confidence: 99%
“…Approaches that integrate molecular sequence data from extant taxa with morphological data from extant and extinct taxa can help our understanding of character evolution and resolve fossil identity in the context of living diversity (e.g., Nylander et al., ). The total‐evidence approach adopted here uses a large molecular alignment (+100k bp) of the Zingiberales (Sass et al., ) with recent work characterizing and describing Zingiberales seed morphology (Benedict et al., ,b, ) to place newly scored Zingiberales fossils.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological data for extant taxa were coded using the characters from Benedict et al. (,b, ) with modifications to remove uninformative characters and minimize character overlap, resulting in 39 morphological characters (Appendix S1, see Supplemental Data with this article). Halopegia azurae (K.Schum.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation